Fordsburg's urban memory - cultural significance and its embodiment in the ordinary landscape - Mayat, Yasmin (School of Architecture, Planning and Geomatics, 2016)
The vibrant suburb of Fordsburg has a rich history of diverse working class communities. It has long been associated with the Indian community and more recently a new immigrant population from the Indian subcontinent. Transitory communities have left their mark on the suburb and have resulted in changing significances and heritage resources. The study's main aim was to identify what constants have gained significance to become anchors for memory and identity in Fordsburg's landscape of rapid urban and social change. An exploration of Fordsburg's history and evolution was undertaken so as to reflect on multiple interpretations and insights into unacknowledged histories of the area. Themes of identity, urban memory, hybridity and the everyday landscape were examined within the context of Fordsburg. It concluded that there are constants of cultural significance which anchor memory and identity. These constants are located in the ordinary urban landscape of public spaces created in Fordsburg's main roads, public amenities and Fordsburg Square.